The SNPs C.513A>T in the MHC B-F gene and rs15001532 in the SPOCK1 gene are associated with Salmonella pullorum disease resistance in chickens - Ze-tang ZHANG; Jian-kang GAN; Wen-wu ZHANG; De-xiang ZHANG; Xi-quan ZHANG; Qing-bin LUO (Journal of Integrative Agriculture, 2016)
This study was designed to identify molecular markers single nucleotide polymorphisms (SNPs) of MHC B-F gene and SPOCK1) associated with Salmonella pullorum disease susceptibility/resistance. A two-stage case-control association study was used. In the first study, a small population comprising 401 Partridge chickens (201 cases and 200 controls) was used, and a total of 118 SNPs genotyped. In the second study, a bigger population comprising 1 075 Partridge chickens (527 cases and 548 controls) was used, and SNPs with significant effect determined in the first study were further analysed. In the first study, 8 SNPs were significantly associated with S. Pullorum disease susceptibility/resistance, however, after further analysis, only the SNPs rs15001532 and C.513A>T were found to be significantly associated with S. Pullorum disease susceptibility/resistance. The relative risk test demonstrated that the AA genotype of rs15001532 resulted in a higher risk of S. Pullorum infection, whereas birds with the TT genotype of C.513A>T were more susceptible to S. Pullorum infection. This research was based on the researches on human complex diseases. With help of these train of thoughts, some common animal diseases can be studied effectively and the process of candidate gene research for animal disease can be improved.